Effects of microbial fermentation on the anti-inflammatory activity of Chinese yam polysaccharides - Yang, Jinchu; Zheng, Yi; Yang, Yongfeng; Huang, Zhenzhen; Sun, Gangchun; Zhao, Renyong; Zhou, Wen-Wen; Cheong, Kit-Leong; Wang, Zichao; Feng, Shouai; Wang, Qiuling; Li, Meng (Frontiers in Nutrition, 2025)
In this study, Chinese yam polysaccharides (CYPs) were fermented using Lactobacillus plantarum M616, and changes in the chemical composition, structure, and anti-inflammatory activity of CYPs before and after fermentation were investigated. The carbohydrate content of L. plantarum M616-fermented CYP (CYP-LP) increased from 71.03% ± 2.75 to 76.28% ± 2.37%, whereas protein and polyphenol content were almost unaffected compared with those of the unfermented CYP (CYP-NF). The monosaccharide composition of CYP-NF included rhamnose, arabinose, galactose, glucose, and mannose in a molar ratio of 0.493:0.6695:0.9738:0.7655:12.4365. CYP-LP had the same monosaccharides as CYP-NF, but the molar ratio was 0.3237:0.3457:0.8278:2.5541:10.4995. Meanwhile, the molecular weight and polydispersity of CYP-LP, respectively, increased from 124.774 kDa and 6.58 (CYP-NF) to 376.628 kDa and 17.928, indicating a low homogeneity. In vitro antioxidant analysis showed that L. plantarum M616 fermentation had varying effects on CYP-LP against DPPH, ABTS, hydroxyl, and superoxide radicals. However, CYP-LP had superior anti-inflammatory activity to CYP-NF and is more effective in regulating superoxide dismutase, catalase, glutathione peroxidase, malondialdehyde, nitric oxide, tumor necrosis factor-α, interleukin-1β, and interleukin-6 release in lipopolysaccharide-induced RAW 264.7 macrophages. This study suggested that CYP-LP is a potential anti-inflammatory ingredient in drugs and functional food.